The Quiet Revolution in Catholic Schooling in Australia - Canavan, fms, Kelvin (Catholic Education: A Journal of Inquiry and Practice, 1998)
In the public policy discourse about vouchers, many Catholic school advocates have been aligned with the new conservative critics of public schools. A review of the Dayton, Ohio, area Catholic schools reveals that need-based student subsidies, which are a variation on vouchers, might reverse the declining urban enrollment in Catholic schools and continue their tradition of educating poor and disadvantaged students. This brief overview of changes in Catholic schooling in Australia over the past 30 years identifies four key factors””the smooth transition from religious to lay staff, the reintroduction of government financial assistance, the development of strong Catholic Education offices, and the steady increase in enrollments””to explain the robust state of Catholic schooling in Australia. However, the case suggests that choice schemes can alter the educational aims of schools in unexpected ways.